Da'wah communication approach to prisoners: The case of Detention Center II B Nganjuk - Rachmanda Lestarini; Luthfi Ulfa Ni’amah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
Da'wah to prisoners requires the right strategic approach. This study aims to find out how da'wah communication strategies are used by da'i in carrying out da'wah among Nganjuk prisoners. The research method used is observation and interviews as well as Miles and Huberman analysis. Research informants were the head of the Nganjuk remand center, lecturers at the detention center, and the prisoners themselves. The results of this study indicate that preachers who are given assignments in detention centers have adequate scientific competence, so that da'wah is in accordance with the mad'u faced (narapida). The majority of inmates in detention centers are those caught in drugs. The average drug case is a teenager. The challenge faced by preachers is the lack of role for prisoners in participating in da'wah activities in detention centers. This is because the inmates' memory has been drained by sedatives. Efforts made by the IIB Nganjuk detention center in implementing da'wah communication within the prisoner's environment are by applying bil lisan (oral da'wah) approach through lectures/recitations, bil qalam through religious books, and bil hal by giving direct examples to inmates. In addition, the most important thing is that the preachers try to understand the psychology or tendencies of each prisoner and not look down on them. This study contributes to the development of da'wah models for groups that are considered marginal. ***Dakwah pada narapidana memerlukan pendekatan strategi yang tepat. Penelitian ini bertujuan untuk mengetahui bagaimana strategi komunikasi dakwah yang digunakan da’i dalam melakukan dakwah di kalangan narapidana Nganjuk. Metode penelitian yang dipakai ialah observasi dan wawancara serta analisis Miless and Huberman. Informan penelitian ialah kepala rutan Nganjuk, penceramah di rutan, dan narapidana sendiri. Hasil dari penelitian ini menunjukkan bahwasanya da’i yang diberikan tugas di Rutan memiliki kompotensi keilmuwan yang memadai, sehingga dakwah menjadi sesuai dengan mad’u yang dihadapi (narapida). Mayoritas narapidana di Rutan ialah mereka yang terjerat narkoba. Rata-rata yang berkasus narkoba ialah manusia yang berusia remaja. Tantangan yang dihadapi da'i adalah kurangnya peran napi dalam mengikuti kegiatan dakwah di rutan. Pasalnya, daya ingat para napi sudah terkuras oleh obat penenang. Upaya yang dilakukan oleh rumah tahanan IIB Nganjuk dalam implementasi komunikasi dakwah di lingkungan narapidana adalah dengan menerapkan pendekatan dakwah bil lisan melalui ceramah/pengajian, bil qalam melalui buku-buku agama, dan bil hal dengan memberikan contoh teladan langsung kepada narapidana. Di samping itu, yang terpenting adalah para da’i berusaha memahami psikologi atau kecenderungan masing-masing narapidana serta tidak memandang mereka rendah. Kajian ini berkontribusi bagi pengembangan model dakwah pada kalangan yang dianggap marjinal.